Charity, social justice and sporting celebrity foundations. Issue 4 (2nd October 2021) - Palmer, Catherine
ABSTRACT: Within the research on sport and social protest, there has been little consideration on the role celebrity foundations might play. Through an analysis of the charity foundations of three of the world's richest and most popular sport stars globally – Roger Federer, David Beckham and Andre Agassi -, this paper maps the potential impacts of their foundations for activism and social justice. The paper argues that it is a particular kind of "soft activism' that sporting celebrities engage in through their philanthropic organisations. Through their foundations, sporting figures operate as well-intentioned celebrities and institutional entrepreneurs who care from afar. Such work does not threaten the hierarchies and inequities built into the institutions of sport but instead legitimate a form of social activism that is fully enabled by and enabling of wider narratives of celebrities 'doing good work'.